2021
DOI: 10.1007/s12264-020-00626-z
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Exosome miR-7239-3p Promotes Glioma Progression by Regulating Circadian Genes

Abstract: Glioma-associated microglial cells, a key component of the tumor microenvironment, play an important role in glioma progression. In this study, the mouse glioma cell line GL261 and the mouse microglia cell line BV2 were chosen. First, circadian gene expression in glioma cells co-cultured with either M1 or M2 microglia was assessed and the exosomes of M2-polarized and unpolarized BV-2 microglia were extracted. Subsequently, we labeled the exosomes with PKH67 and treated GL261 cells with them to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 31 publications
(30 reference statements)
0
22
0
Order By: Relevance
“…In line with these results, a more recent study has shown that microglia derived OLFML3 acts as a paracrine factor that facilitates glioma invasion [ 42 ]. Moreover, this idea is further supported by the recent finding that microglial exosomes and miRNA have been found to induce glioma progression by regulating circadian genes [ 41 ]. In turn, Dong et al have proposed to target GSCs through disruption of their circadian clock [ 174 ].…”
Section: Molecules Promoting Survival Of Glioma Stem Cellsmentioning
confidence: 80%
“…In line with these results, a more recent study has shown that microglia derived OLFML3 acts as a paracrine factor that facilitates glioma invasion [ 42 ]. Moreover, this idea is further supported by the recent finding that microglial exosomes and miRNA have been found to induce glioma progression by regulating circadian genes [ 41 ]. In turn, Dong et al have proposed to target GSCs through disruption of their circadian clock [ 174 ].…”
Section: Molecules Promoting Survival Of Glioma Stem Cellsmentioning
confidence: 80%
“…Then, transmission electron microscopy (TEM) was utilized to identify exosome morphology. Besides, bicinchoninic acid (BCA) protein assay (Solarbio, China) was applied for the measurement of the protein content; Western blot for the detection of the expression of exosome-specific markers CD63 and HSP70; and Nanoparticle Tracker (NTA) system for determination of the size of vesicles [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Figueroa et al found that miR-1587 could be transferred by glioma related-mesenchymal stem cells (GA-hMSCs) to glioma stem-like cells (GSCs) via exosomes and increased GSC proliferation and clonogenicity to maintain a GSC-supportive niche via directly targeting the expression of nuclear receptor co-repressor-1 (NCOR1) (25). Li et al also revealed that miR-7239-3p, released by M2 microglial exosomes, could enter glioma cells via endocytosis, resulting in the repression of brain and muscle ARNT-like protein-1 (Bmal1) expression and facilitating glioma cells proliferation and migration (26). In addition, the molecule mechanisms of exosomal miRNA in medulloblastoma (MB), another subtype of glioma, have been recently investigated.…”
Section: Exosomal Mirnas and Proliferation Of Gliomamentioning
confidence: 99%